Major Theories Underlying Assessment Practices in Language Classrooms - AKNOUCH, Layla (Revue Internationale du Chercheur, 2022)
Assessment is one of the most critical components of education, and like any other aspect of language learning and teaching, assessment has been influenced by a number of theories. Each of these learning theories has resulted in considerable changes in the ways that assessment practices are viewed and carried out in the field of second and foreign language teaching and learning. Accordingly, this paper seeks to provide a concise outline of the major theories of learning and schools of thought that have had an influence on educational assessment practices in the context of second and foreign language learning and teaching. More specifically, the current paper discusses four major theories of learning namely behaviorism, cognitivism, constructivism, and multiple intelligences. The paper aims also to explain how assessment practices in the context of second and foreign language teaching and learning have changed both in their focus and in their methods on the basis of these learning theories.